2022
DOI: 10.1126/science.abm6509
|View full text |Cite
|
Sign up to set email alerts
|

Total synthesis of himastatin

Abstract: The natural product himastatin has an unusual homodimeric structure that presents a substantial synthetic challenge. We report the concise total synthesis of himastatin from readily accessible precursors, incorporating a final-stage dimerization strategy that was inspired by a detailed consideration of the compound’s biogenesis. Combining this approach with a modular synthesis enabled expedient access to more than a dozen designed derivatives of himastatin, including synthetic probes that provide insight into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 53 publications
(107 reference statements)
0
7
0
Order By: Relevance
“…Very recently, Movassaghi et al reported the synthesis of this bispyrroloindoline scaffold by the radical dimerisation of pyrroloindoline with an excess of silver oxidant. 16 These transformations show that the current methodology is potentially useful for organic synthesis.…”
Section: Resultsmentioning
confidence: 89%
“…Very recently, Movassaghi et al reported the synthesis of this bispyrroloindoline scaffold by the radical dimerisation of pyrroloindoline with an excess of silver oxidant. 16 These transformations show that the current methodology is potentially useful for organic synthesis.…”
Section: Resultsmentioning
confidence: 89%
“…thermotolerans SCSIO 00652, and its biosynthetic pathway had been elucidated by our group in 2012 . Himastatin, isolated from Streptomyces hygroscopicus ATCC 53653, is a cyclohexadepsipeptide antibiotic with a novel structure and significant cytotoxic and antibacterial activities. , As aforementioned, to verify the expression of these three constructed strains, MGCEP 1.0/ dsa , MGCEP 1.0/ mpn , and MGCEP 1.0/ hmt were fermented independently under the same conditions with the control strain MGCEP 1.0, and HPLC results indicated that three new peaks appeared in MGCEP 1.0/ dsa (Figure A, trace iii), two new peaks were observed in MGCEP 1.0/ mpn (Figure A, trace iv), and one new peak was found in MGCEP 1.0/ hmt (Figure A, trace v) compared to that in MGCEP 1.0, respectively. To analyze the molecular weight of these new peaks, the same strategy was used as aforementioned.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Following incubation at 28 °C for 3–5 days, apramycin-resistant (Apr R ) exoconjugants were identified and the genomic DNA of the mutant strains was further screened by PCR using the appropriate primers to obtain valid heterologous expression engineered strains (Figures S72–S81). In addition, plasmids pSET152AB/cosmid-142H (harboring the BGC of A201A), pSET152AB/cosmid-079A (harboring the BGC of desotamides), pSET152AB/cosmid-12H8 (harboring the partial BGC of himastatin), pBAC2I22 (harboring the BGC of actinopyrone), pSET152AB/cosmid-76F (harboring the BGC of abyssomicin), pSET152AB/cosmid-179F (harboring the BGC of grincamycins), pHZAUFXJ-3-J11 (harboring the BGC of kendomycin), and pBAC23H2 (harboring the BGC of elaiophylin) have been constructed and described in our previous research.…”
Section: Methodsmentioning
confidence: 99%
“… 17 ; D’Angelo et al. 18 ) and by Knowles’ photo-iridium driven capture of pyrroloindoline carbocation (Gentry et al. 19 ).…”
Section: Before You Beginmentioning
confidence: 99%